Continuous Heavy Rainfall and Wind Velocity During Flowering Affect Rice Production - Edi Santosa; Herdhata Agusta; Dulbari Dulbari; Dwi Guntoro; Sofyan Zaman (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
To mitigate the impact of extreme weather incidents, rice cultivars Way Seputih (WS) and Way Apo Buru (WAB) were evaluated under simulation of continuous wind and rainfall treatments. The research was conducted from July to October 2017 at Leuwikopo Experimental Farm, Bogor, Indonesia. For 15 days at day time, flowering rice hills were treated with about 100 mm/h water shower (Experiment-1), and with 0, 10-15, 20-25 and 35-40 km/h wind velocity (Experiment-2). Results showed that wind and rainfall treatments reduced rice production; the effect depended on the genotypes and flowering stage. Rain treatment from panicle emergence to 50%-emerged increased the number of unfilled grains by 154.6-182.3% and 55.7-101.9% in WS and WAB cultivars, respectively. Rain treatment at 100%-emerged had no effect on WS, but it increased unfilled grain (163.5%) and decreased grain index (12.9%) in the WAB cultivar. Wind speed at 35-40 km/h promoted a high percentage of grain drop (25.7%) and unfilled grains (77.3%), and low grain index (20.8 g) in WS genotype. WAB was more tolerant of wind stress than the WS. The present experiment showed that genotype had different responses to wind and rain treatments implying different mitigation strategies should be applied through genotype selection.